Different forms of Euler’s theorem forhomogeneous functions to solve partial differential equation - et. al., Amit Kumar, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this paper we will discuss Euler’s theorem for homogenous functions to solve different order partial differential equations. We will see that how we can predict the solution of partial differential Equation using different approaches of this theorem. In fact we also consider the case when more than two independent variables will be involved in the partial differential equation whenever dependent functions will be homogenous functions. We will throw a light on one method called Ajayous rules to predict the solution of homogenous partial differential equation.